Integrasi Media Teknologi Untuk Meningkatkan Kemampuan Bahasa Anak Usia Dini - Suraya Suraya; Fitry Maharani Siagian (Universitas Maritim AMNI Semarang, 2024)
Integrating internal information technology media with language acquisition can provide information that improves skills and language acquisition, especially in early childhood. This research method uses a systematic literature review. Data collection was carried out by documenting and reviewing all papers related to education for the 2018-2023 period. Articles Used In this research, 36 domestic journal articles and certified articles from Google Scholar, Research Gate, SINTA, and DOAJ were obtained. Based on this research, the data shows that the integration of technological media in learning can stimulate young children's interest, attract their attention, make children happier, increase their learning motivation, and accelerate language acquisition.